Предмет: Алгебра,
автор: elizabetlev
Пусть x1 x2 - корни уравнения (x-2)^2+24=(2+3x)^2.Чему равно (х1+х2)*(-6)?
Ответы
Автор ответа:
0
решение
Действие 1
x²-2*2*x+4+24=4+2*2*3x+9x²
x²-4x+24=9x²+12x+4
8x²+16x-20=0 |:4
2x²+8x-5=0
D=8²-4*2*-5=64+40=144
x1=-8+12/2*2=4/4=1
x2=-8-12/2*2=-20/4=-5
Действие 2
Если х1=1, х2=-5, то (х1+х2)*(-6)=(1*1+(-5)*2)*(-6)=(1-10)*(-6)=9*(-6)=-54
Ответ:-54
Похожие вопросы
Предмет: География,
автор: leilac0506
Предмет: Английский язык,
автор: sofi3116
Предмет: Математика,
автор: Ернур11111111
Предмет: История,
автор: Stasianchic
Предмет: Биология,
автор: Sisi12